Sensory expectations elicited by the sounds of opening the packaging and pouring a beverage. Issue 1 (December 2015) - Spence, Charles; Wang, Qian
Abstract The majority of the literature on sensory expectations has focused solely on those that are set by the eye, that is, by what we see. However, although we rarely think about it, the sounds we hear prior to tasting also influence both our sensory expectations concerning what a food or beverage product will taste like and our hedonic expectations concerning how much we think that we are going to enjoy the experience. In this article, we focus on the perception of beverages and consider just what information is potentially conveyed to the mind of the consumer by the sounds of opening (the packaging), pouring the liquid, and even the sounds of carbonation of a drink in a glass or other receptacle. We review the research that has investigated whether people can discriminate the temperature of a beverage, the level and/or type of carbonation, the viscosity of the liquid, and even the shape of the bottle or container by sound alone. Finally, we look at the question of whether certain beverages do, or could possibly, have a signature sound of opening, and at the opportunities associated with the modification of product sounds in beverage advertisements in order to help emphasize certain specific product or brand attributes.